EFFECT OF FOLIAR SPRAY OF NUTRIENT AND PLANT GROWTH REGULATORS ON GROWTH AND YIELD OF GREEN GRAM (Vigna radiata L.) - D.S.V.S .SRUTHI; SHIKHA SINGH; DHANANJAY TIWARI; P.KAVYA (The Bioscan, 2020)
An experiment was carried out during Zaid season of 2019 at Crop Research Farm, NAI, SHUATS to study about the Effect of Foliar spray of Nutrient and Plant Growth Regulators on growth and yield of Greengram (Vigna radiata L.). The experiment consisted of 9 treatments which includes No spray (Control), Foliar spray of DAP alone, Salicylic Acid alone and combination of DAP, Salicylic Acid and NAA and the combination of DAP and Salicylic Acid.Results revealed that foliar spray of 1% DAP + 100 ppm Salicylic Acid twice at 25 and 45 days after sowing recorded the maximum Plant height (33.48 cm), dry matter accumulation (82.47 g/m2), number of pods/ plant (55.60), number of grains/pod (9.93), test weight (36.84), grain yield (855.55 kg/ha), stover yield (2233.33 kg/ha) in greengram. As well as, the maximum number of nodules was obtained with 1% DAP (7.33) which was closely followed by 1% DAP+100 ppm Salicylic Acid (7.11) and the maximum Crop Growth Rate and Relative Growth Rate (0.99 g/m2/day and 0.006 g/g/day respectively) was obtained with 2% DAP. However, Net returns (65577.54 ¹ /ha) and B:C ratio (1.69) was also obtained maximum with the application of 1% DAP+100 ppm Salicylic Acid.